DEVELOPING LOCAL WISDOM – BASED FINGER PUPPET MEDIA TO IMPROVE STUDENTS’ SPEAKING SKILLS AT GRADE IV - Nurkholisoh Agustiani; Rina Yuliana; M Taufik (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Speaking skill refers to students’ ability to convey their ideas. This research employed a questionnaire method within an R&D design, supported by data collection through observation and interviews. The purpose of this study was to produce feasible (valid) local-wisdom–based finger puppet media for improving the speaking skills of fourth-grade students at SDN Cikande Permai. This study used the R&D model proposed by Sugiyono (2010: 409), which consists of six steps: (1) problem analysis, (2) data collection, (3) product design, (4) design validation, (5) design revision, and (6) product testing. The product was tested on one teacher and 10 fourth-grade students. The validation results from material experts reached 87%, from linguists 84%, and from media experts 83%, all of which were categorized as very feasible, indicating that the product could be used as learning media. Furthermore, field trials were conducted through students’ response questionnaires, yielding a score of 93.7% in the very good category. Thus, it can be concluded that the local-wisdom–based finger puppet media is feasible for use in learning.